2002
DOI: 10.1590/s0101-81752002000500021
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and importance of spiders inhabiting a Brazilian sugar cane plantation

Abstract: ABSTRACT. The spider fauna (Araneae) of a sugar cane plantation was surveyed monthly by hand collection and beating vegetation in sugar cane fields across Botucatu, State of São Paulo, Brazil. Composition and richness (family and species where identification to species was possible) microhabitat preferences were recorded, and diversity and evenness indices were calculated. A total of 1291 spiders belonging to 73 species and 20 families were collected. The most diverse families were Theridiidae, Salticidae, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Although P. vellutinus inhabited type‐N bromeliads ( Bromelia and Ananas ), this species also occurred at a high frequency on other monocotyledonous plants, especially sugarcane. In other studies, several individuals of P. vellutinus were collected on sugarcane (Rinaldi & Forti 1997, Rinaldi et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although P. vellutinus inhabited type‐N bromeliads ( Bromelia and Ananas ), this species also occurred at a high frequency on other monocotyledonous plants, especially sugarcane. In other studies, several individuals of P. vellutinus were collected on sugarcane (Rinaldi & Forti 1997, Rinaldi et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
“… Source: e Rossa‐Feres et al . (2000), f Romero & Vasconcellos‐Neto (2005a,b,c), g Höfer & Brescovit (1994), h Rinaldi & Forti (1997), Rinaldi et al . (2002), i Romero & Vasconcellos‐Neto (2004b), j Lise & Braul‐Jr.…”
Section: Methodsmentioning
confidence: 99%
“…There are few data comparing areas with these two surrounding matrices and their possible effects to the biota. Rinaldi et al [20] found a surprisingly high richness of spiders on sugarcane plantations. Ott et al [21] sampled spiders on herbaceous vegetation in two different citrus orchards, "traditional" and "ecological," and despite the differences in cultivation practices, they found a lower richness than Rinaldi et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Ott et al [21] sampled spiders on herbaceous vegetation in two different citrus orchards, "traditional" and "ecological," and despite the differences in cultivation practices, they found a lower richness than Rinaldi et al [20]. Ott et al [21] also did a survey on citrus trees of the "ecological" orchard, and there they found a greater richness of spiders species than Rinaldi et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although many spider species tend to occur across a wide range of habitats, associations among species seem to vary in a predictable manner across different vegetation types (TURNBULL, 1973;UETZ, HAJAJ & CADY, 1999). Studies conducted in various agricultural systems have shown that spiders are not randomly distributed in this habitat (TOPPING & LÖVEI, 1997;SAMU, SUNDERLAND & SZINETÁR, 1999;HALAJ, CADY & UETZ, 2000b;RINALDI, PRADO & CADY, 2002). The occurrence of spider species in species of plants localized in patches distant geographically, is an interesting situation for analyze the association between spiders and vegetation.…”
mentioning
confidence: 99%